2001
DOI: 10.1007/s002100100484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetaminophen on monoaminergic systems in the rat central nervous system

Abstract: Although acetaminophen is a well established analgesic, its mechanism of action is still unknown. We investigated whether this drug could affect central monoaminergic neurotransmission in rats. Significant increases in serotonin (5-HT) levels were found in the posterior cortex, hypothalamus, striatum, hippocampus and brain stem, but not spinal cord, 45 min after per os administration of 200-400 mg/kg of acetaminophen. However, this treatment altered neither the levels of 5-hydroxyindoleacetic acid nor the accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 21 publications
5
45
0
Order By: Relevance
“…8) Consistent with these findings, depletion of serotonin and central administration of serotonergic antagonists inhibit the antinociceptive effect of AcAP in rats and mice. 5,7,[9][10][11] Also in humans, tropisetron and granisetron block the analgesic effect of AcAP.…”
Section: 5)supporting
confidence: 55%
See 1 more Smart Citation
“…8) Consistent with these findings, depletion of serotonin and central administration of serotonergic antagonists inhibit the antinociceptive effect of AcAP in rats and mice. 5,7,[9][10][11] Also in humans, tropisetron and granisetron block the analgesic effect of AcAP.…”
Section: 5)supporting
confidence: 55%
“…8) However, it also has been shown that serotonin efflux in the hypothalamus of clorgiline-treated mice rises 11-fold when the body temperature is lowered by 5-hydroxytryptophan administration, 28) and thus the increase of brain serotonin by AcAP seems to be far from this level. The serotonin-non-dependence of AcAP-induced hypothermia suggests that the mechanism responsible for the hypothermic action of AcAP differs from that underlying the mechanism responsible for analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, ASA increases 5-HT content in the cerebral cortex and pons [50,51], as does acetaminophen in the striatum, posterior cortex, hypothalamus, hippocampus and brain stem but not the spinal cord of rats [52]; while rofecoxib increases 5-HT in the frontal cortex [53]. Lysine ASA increases concentrations of 5-hydroxyindole acetic acid, in several areas of the brain in rats [54].…”
Section: The Serotonergic System and Its Relation To Non-opioidsmentioning
confidence: 96%
“…For example, PAR can protect primary rat embryonic DA neurons from glutamate toxicity. Also, PAR administration 2 International Journal of Electrochemistry at antinociceptive doses affects serotonin (5-HT) and dopamine levels in various brain areas and the spinal cord in rate [9].…”
Section: Introductionmentioning
confidence: 99%